Industry Interactions and Their Influence on Dreams, Goals, Work Interests, and Vocational Attitude of Sport Industry Job Seekers - Jiayao C Qi; Samuel Y Todd (Journal of Applied Sports Management, 2023)
The sport industry is filled with passionate job seekers (e.g., Todd & Andrew, 2008) who often craft lofty future work desires and idyllic dreams (Odio et al., 2014). But little is known about how these are shaped over time. Previous studies noted how plans of sport job seekers often change after encountering realistic information about the actual work in sport (Koo et al., 2016; Todd & Magnusen, 2014). This urges a closer examination of the way in which sport job seekers interact with the industry in a continuous, iterative way, and how that impacts vocational attitude and imaginations. Findings suggest that industry interaction are positively related to job seeker’s future work self, career identity, career optimism, and negatively related to career reconsideration. Implications to sport industry human resource managers are discussed.
Keywords: industry interaction; vocational attitude; career identity; future work self; career optimism; career reconsideration